Widgets baseados em conhecimento advindo de dados referenciados e abertos na Web - Santos, Henrique; Furtado, Vasco; Pinheiro, Vládia; Ferreira, Caio; Vasconcelos, José Eurico; Shiki, Guilherme (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
The use of widgets is a very popular manner to make a website customization. From widget’s creation the content creator configures the website with functions that he/she consider adequate to the users. Typically, widgets relies on syndication (RSS) in which a website content is made available to other websites. Even though there is a huge popularity of this kind of widgets, they typically are constrained to what a data provider makes available. Linked Open Data (LOD) is an opportunity to cope with the today’s constraint in the process of widget creation and execution. We propose a platform, called SemWidgets (from Semantic Widgets), for the creation and execution of piece of programs able to access and reason over LOD. With SemWidgets, we provide to the content producer of a website a way to describe the concept(s) that best represent the content to be explored. Widgets created from SemWidgets have the power to perform inferences and access external sources that constitute information that may be useful and appropriate to the context of the website.